Green biosynthesis of silver and gold nanoparticles using Teak (Tectona grandis) leaf extract and its anticancer and antimicrobial activity - Huda Mahdi Younis; Hanaa Ali Hussein; Fatin L. Khaphi; Zahra Kadhum Saeed (Heliyon, 2023)
The green synthesis of nanoparticles (NPs) utilizing a green path is eco-friendly and profitable compared to traditional physical and chemical techniques. This research conducted a green synthesis of gold NPs (AuNPs) and silver NPs (AgNPs) using an extract of Teak (Tectona grandis) and their anticancer and anti-microbial activities. Various techniques like transmission-electron microscopy (TEM), UV–Vis spectroscopy, thermal-gravimetric analyses (TGA), X-ray diffraction (XRD), and Fourier transform-infrared spectroscopy (FT-IR) were used to analyze synthesized AuNPs and AgNPs. The effects of different factors like the amount of extract used, solution pH, and contact time were measured to obtain the best possible conditions for synthesizing NPs. The AgNPs showed significant anticancer activity against HepG2 with an IC50 of 6.17 mg/ml compared to Teak extract (>50 mg/ml) and AuNPs (44.1 mg/ml), while AuNPs (6 % Teak extract and 2.9 × 10−3 M HAuCl4) showed significant antibacterial and antifungal activity against Pseudomonas aeruginosa, Aspergillus niger, Bacillus subtilis, and Escherichia coli with an inhibition zone of 11 mm, 12 mm, 12.5 mm, and 15.5 mm, respectively as compared to other treatments. These findings confirmed the medical applications of AuNPs and AgNPs and might open new possibilities in this field.